Adverse events following immunisation with a meningococcal serogroup B vaccine: report from post-marketing surveillance, Germany, 2013 to 2016 - Mentzer, Dirk (Euro Surveill, 2018)
In January 2013, a novel vaccine against Neisseria meningitidis serogroup B, the multicomponent meningococcal serogroup B vaccine (4CMenB), was approved by the European Medicines Agency. We aimed to evaluate the safety profile of this vaccine. Methods: All adverse events following immunisation (AEFI) reported from Germany since the vaccine’s launch in Germany in November 2013 through December 2016 were reviewed and analysed. Results: Through December 2016, a total of 664 individual case safety reports (ICSR) notifying 1,960 AEFI were received. A majority of vaccinees for whom AEFI were reported were children 2 to 11 years of age (n = 280; 42.2%) followed by infants and toddlers aged 28 days to 23 months (n = 170; 25.6%). General disorders and administration site conditions was the System Organ Class (SOC) with the majority of AEFI (n = 977; 49.8%), followed by nervous system disorders (n = 249; 12.7%), and skin and subcutaneous tissue disorders (n = 191; 9.7%). Screening of patient records for immune-mediated and neurological diseases did not raise any safety signal in terms of an increased proportional reporting ratio (PRR). Conclusions: The safety profile described in the Summary of Product Characteristics, in general, is confirmed by data from spontaneous reporting. No safety concerns were identified.